Physio-biochemical Response of Labeo rohita (Hamilton, 1822) fed with Antifungal Drug, Fluconazole - Saha, Himadri; Pal, Asim Kumar; Sahu, Narottam Prasad; Saha, Ratan Kumar; Goswami, Pritam (Fishery Technology, 2018)
An experiment was carried out to delineate the biochemical responses in Labeo rohita fingerlings fed with fluconazole (FLZ). There were twenty-four treatments divided into four groups (Control, T1, T2, and T3 fed with 0, 10, 20 and 30 mg FLZ kg-1 body weight, respectively) and each group with 6 exposure times (0, 6, 12, 24, 48, and 96 h) in triplicates. Biochemical parameters in plasma like glutamate oxaloacetate transaminase (GOT), glutamate pyruvate transaminase (GPT), alkaline phosphatase (ALP), glucose, albumin, albumin globulin ratio (A/G) were measured. Significant increase (p<0.05) in the GOT, ALP, and decrease (p<0.05) in glucose were observed in the treatment groups as compared to control. However, homeostasis was achieved by rohu within 48 h of administration. Fish fingerlings treated with fluconazole at higher doses exhibited marked changes in physiology.